Study of blood group and platelet counts in ER and ENT patients with epistaxis - Binita Pradhan; Raunak Bista; Bharat Kumar Bhattarai; Ashaya Luitel; Sujan Pandey; Sailesh Pradhan (Journal of Pathology of Nepal)
Background: Epistaxis is one of the most common emergencies and a very difficult problem to tackle especially in Primary Health Centers or Health Posts in rural areas of Nepal. The objective of the study was to identify blood group and platelet count with the occurrence of nasal bleeding.